An ontology based for drilling report classification - Guilherme, Ivan Rizzo; de Souza Serapiao, Adriane Beatriz; Rabelo, Clarice; Pelaquim Mendes, Jose Ricardo (Springer, 2006)
This paper presents an application of an ontology based system for automated text analysis using a sample of a drilling report to demonstrate how the methodology works. The methodology used here consists basically of organizing the knowledge related to the drilling process by elaborating the ontology of some typical problems. The whole process was carried out with the assistance of a drilling expert, and by also using software to collect the knowledge from the texts. Finally, a sample of drilling reports was used to test the system, evaluating its performance on automated text classification.